Elevers vurdering av politikeres bruk av sosiale medier i et postfakta-samfunn og implikasjoner for samfunnsfaget - Mathé, Nora E.H.; Elstad, Eyvind (Nordidactica. Journal of Humanities and Social Science Education, 2017)
In the age of political confrontation the public is at times presented with statements in the media that are less than truthful. At the same time, social media create new arenas for political communication. These trends implicate that today’s students need to develop critical awareness, but also experience with factual argumentation about political issues to develop political understanding and their own viewpoints. The purpose of this article is to explore how Norwegian 16-17-year-old students perceive and evaluate some examples of politicians’ communication in social media, and to discuss the need for social studies to provide students with sufficient prerequisites for meeting an ever-changing future. We make use of theory on rational behaviour as well as theory on deliberative and radical democracy to shed light on the student data. The analysis shows that the students are critical of politicians’ use of social media. Further, they judge their own information evaluation abilities too positively. Implications for social studies are discussed: Students should practice political discussion and argumentation and the focus on critical analysis of political communication should be further strengthened.